Endangered Species Act (ESA) in the 109th Congress : Conflicting Values and Difficult Choices. (U.S. Congressional Research., 2006)
Examines controversial provisions of the Endangered Species Act (ESA) affecting the use of Federal and nonfederal lands and resources. Reviews major domestic and international provisions of the ESA, evaluates the efficacy of species protection and restoration efforts, and examines ESA issues in the 109th Congress and additional legislative initiatives.